THE PRELIMINARY RULING PROCEDURE AND THE IDENTITY REVIEW - Drinóczi, Tímea; Mohay, Ágoston (EU and comparative law issues and challenges series (ECLIC), 2018)
Constitutional identity, as enshrined in Article 4(2) TEU might theoretically open up the possibility for EU Member States to refuse fulfilling certain obligations under EU law by referencing certain, as if yet not clearly defined elements of constitutional identity. Member States’ constitutional identity, which is to be respected by the EU does not appear in positive law. Having regard to multilevel constitutionalism, it may be assumed that national constitutional identity will be elaborated in dialogues between national (constitutional) courts and the Court of Justice of the European Union. Based on previous practice however, the national and European interpretations of identity differ significantly. To achieve necessary convergence, the Court of Justice and national courts must cooperate in interpreting the concept of constitutional identity. This raises the necessity of examining whether the procedural prerequisites of this cooperation are given in national and EU public law. The questions to be examined are 1) whether the preliminary ruling procedure has already been used in identity-related cases, 2) what the position of constitutional courts/supreme courts (courts engaged in constitutional interpretation) is regarding the preliminary ruling procedure and 3) whether this may be considered the appropriate procedure when applying Article 4(2) TEU or would it require modification?